2006
DOI: 10.1200/jco.2006.24.18_suppl.7085
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan (I), carboplatin (C), and radiotherapy (RT) followed by maintenance bevacizumab (B) in the treatment (tx) of limited-stage small cell lung cancer (LS-SCLC): Update of a phase II trial of the Minnie Pearl Cancer Research Network

Abstract: 7085 Background: Targeting VEGF has proven to be an effective tx strategy in many solid tumors including non-small cell lung cancer. VEGF expression in SCLC provides rationale for studying B in addition to chemoradiotherapy. Methods: The endpoints of this multicenter community-based study were to assess the safety, response rate (RR), and progression-free survival (PFS) of I/C/RT followed by B in patients (pts) with LS-SCLC. Tx included: C AUC = 5 IV D1, I 50mg/m2 IV D1,8 Q 21D x 4 cycles, and RT 1.8 Gy daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…However, our current data showed that it was difficult to ascertain whether addition of endostatin was efficacious in treating these patients and whether there was a synergy of endostatin plus radiation therapy. The median PFS and OS estimated at 10 and 14 months, respectively, were similar to those of previous clinical trials of CRT alone [ 1 , 2 , 4 – 6 , 10 , 16 ]. Whether the inconsistent schedule of endostatin from other studies made our work unsuccessful is worthy of more research.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, our current data showed that it was difficult to ascertain whether addition of endostatin was efficacious in treating these patients and whether there was a synergy of endostatin plus radiation therapy. The median PFS and OS estimated at 10 and 14 months, respectively, were similar to those of previous clinical trials of CRT alone [ 1 , 2 , 4 – 6 , 10 , 16 ]. Whether the inconsistent schedule of endostatin from other studies made our work unsuccessful is worthy of more research.…”
Section: Discussionsupporting
confidence: 82%
“…However, endostatin has toxicity concerns and may cause development of tracheoesophageal/bronchial fistulae in NSCLC patients, but this is generally an uncommon event resulting from CRT of lung cancer. In a simultaneous and ongoing study in limited stage SCLC, among 29 patients there were 2 confirmed and 1 suspected episode of tracheoesophageal/bronchial fistulae [ 16 , 17 ]. All 3 patients had grade III esophagitis during CRT and bevacizumab treatment (another tumor angiogenesis inhibitor that is a humanized monoclonal antibody directed against VEGF).…”
Section: Discussionmentioning
confidence: 99%
“…3,4,14,20,21 The recent success of adding bevacizumab to standard chemotherapy regimens in several solid tumor settings (colorectal, non-small cell lung, and breast) has encouraged the development of bevacizumab in other treatment settings, including SCLC. [5][6][7]11 The role of angiogenesis in SCLC is unknown, although some preclinical models suggest this may be a useful target. 8 -10 Our center previously conducted a phase II study using bevacizumab in a maintenance role, but found little benefit for this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 Our center previously conducted a phase II study using bevacizumab in a maintenance role, but found little benefit for this strategy. 11 Other centers have similarly found no benefit to a maintenance strategy using the angiogenesis inhibitors thalidomide or vandetanib. 22,23 The present trial was planned to introduce bevacizumab earlier in treatment by administering it concurrently with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation